Implementasi Cloud Computing Cluster Menggunakan Microstack Untuk Layanan Web - Ridha, Muhammad Arif Fadhly; Gunawan, Khairul (Politeknik Caltex Riau, 2023)
Cloud Computing is a network/internet-based computerized system, where resources, software, information and applications are provided for use by other computers in need. Cloud Computing is often used by companies to support the company's web services. The problem that is often experienced in cloud computing is downtime. Where this problem occurs because the file system or web server is an error and does not have a backup. This problem can be overcome by means of cloud computing cluster techniques that can provide web services that have high availability. Clusters consist of different servers working together to ensure that downtime of critical resources is reduced to a minimum with the aim of ensuring that critical resources reach maximum availability which is known as high availability. For the implementation of cloud computing clusters, we need a platform that has tools that can support these needs. One of the platforms that can be used is OpenStack, OpenStack is a free software and open-source software platform for cloud computing, mostly used as Infrastructure as a Service (IaaS) . One of the packages released by OpenStack is MicroStack which contains tools from OpenStack to build clusters in cloud computing. The result of this research is the achievement of high availability on web server services where web services can still be accessed when two nodes are turned off and when one of the servers is turned off. CPU usage increases when there are multiple number of http requests when multiple nodes are shut down and also when one of the physical servers is shutting down. Memory usage also increases when multiple nodes are shut down and also when one of the physical servers is shutting down.